2019
DOI: 10.4236/as.2019.105049
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Angiotensin-Converting Enzyme before and after Cryopreservation of Gir Semen

Abstract: The aim of this study was to characterize the angiotensin-converting enzyme (ACE) in Gir semen before and after cryopreservation. The ejaculate of five sexually mature bulls was used. After collection, one 1-mL aliquot of fresh semen was analyzed immediately, and the rest of the semen was cryopreserved in liquid nitrogen for subsequent analysis. Freshly collected semen and thawed cryopreserved semen were centrifuged twice with Tyrode's albumin lactate pyruvate medium (TALP) to remove plasma and extender, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Spermadhesin 2 (spermadhesinZ13) which is a protein with a coding gene located on the 26 th chromosome in cattle is reported to have a negative impact on fertility, reduces sperm motility, and is expressed in many low fertility cattle [35,49]. Štiavnická et al [50] found that a high ubiquitin protein in cow sperm is closely related to quality and low fertility in bulls.…”
Section: Plasma Seminal Proteinsmentioning
confidence: 99%
“…Spermadhesin 2 (spermadhesinZ13) which is a protein with a coding gene located on the 26 th chromosome in cattle is reported to have a negative impact on fertility, reduces sperm motility, and is expressed in many low fertility cattle [35,49]. Štiavnická et al [50] found that a high ubiquitin protein in cow sperm is closely related to quality and low fertility in bulls.…”
Section: Plasma Seminal Proteinsmentioning
confidence: 99%